Feasibility of LoRa Implementation for Remote Weather Monitoring System through Field Measurement and Case Study Analysis - Abd Rahman, N.H.; YAMADA, Y.; HUSNI, M. H.; ABDUL AZIZ, N. H. (International Journal of Integrated Engineering, 2018)
This paper discusses the feasibility of Long Range Wide-area network (LoRa-WAN) implementation for weather data collection and transmission in remote locations, specifically in east Malaysia. Currently, Malaysia Meteorological Department (MetMalaysia) has installed more than 100 weather stations around Malaysia, and out of this number, there are many stations, mostly in east Malaysia that are dependent on Very Small Aperture Terminal (VSAT) services for data transmission due to unavailability of mobile coverage. Due to significant cost of VSAT subscription, LoRa communication is proposed as an alternative solution due to its low power, low-cost, and long range characteristics. In this paper, the study has been performed through two stages; first, technical performance of LoRa network was validated through field measurement in urban areas to determine the actual LoRa characteristics in real condition. In the measurement, a LoRa module operating at 433 MHz was used to demonstrate a single channel LoRa gateway that acted as a bridge to communicate between LoRa node to IP network. Parameters such as received power spectrum and free space path loss were recorded for analysis. Second, based on the measured data, extrapolation of maximum feasible distance of LoRa signal propagation was done to analyze the viability of implementing LoRa in various locations of existing weather stations in Sabah and Sarawak. Two case studies are presented in this paper, with the aim to evaluate the suitable location of LoRa gateway to establish communication with the existing weather stations when LoRa network is used. Detailed link budget analysis was performed for each scenario. Based on the comparison between theoretical and measurement, the power transmitted from LoRa node shows inconsistent readings throughout the day, suspected due to the changes in spread factor that has been automatically set by the module. Nevertheless, taking into account this factor, it was found that the transmission range was adequate for some remote locations. Meanwhile, for some locations that are separated too far from each other, higher power is needed to allow consistent communication.